Mengembangkan Kreativitas Anak-Anak Berkebutuhan Khusus - Ria Triayomi; Petrus Murwanto; Lisnani; Theresia Widyastuti; Dewi Sri; Vincentia Dyah Ayu Sasmita (CV. Creative Tugu Pena, 2024)
Palembang City YPAC School is one of the extraordinary schools under the auspices of the YPAC foundation. Students who are active at this school are students who are deaf, mentally disabled, blind, physically impaired, autistic and Down syndrome. This service aims to determine: 1) the level of creativity of students with special needs at YPAC Palembang; 2) The methods used by teachers in developing the creativity of students with special needs at SLB YPAC. Activities for 2 days with the materials provided, namely handicrafts in the form of face painting, finger painting, thread pulling painting, singing together, and entrepreneurship seminars for teachers and parents of students. As a result of this service activity, the level of participant satisfaction with PkM activities was responded to by agreeing at 57.20% and strongly agreeing at 39.51%.